Examining Japan's lost decades (Routledge contemporary Japan series, 2015)
"This book examines five features of Japan's 'Lost Decades': the speed of the economic decline in Japan compared to Japan's earlier global prowess; a rapidly declining population; considerable political instability and failed reform attempts; shifting balances of power in the region and changing relations with Asian neighbouring nations; and the lingering legacy of World War Two. Addressing the question of why the decades were lost, this book offers 15 new perspectives ranging from economics to ideology and beyond. Investigating problems such as the risk-averse behaviour of Japan's bureaucracy and the absence of strong political leadership, the authors analyse how the delay of 'loss-cutting policies' led to the 1997 financial crisis and a state of political gridlock where policymakers could not decide on firm strategies that would benefit national interests. To discuss the rebuilding of Japan, the authors argue that it is first essential to critically examine Japan's 'Lost Decades' and this book offers a comprehensive overview of Japan's recent 20 years of crisis. The book reveals that the 'Lost Decades' is not an issue unique to the Japanese context but has global relevance, and its study can provide important insights into challenges being faced in other mature economies. With chapters written by some of the world's leading Japan specialists and chapters focusing on a variety of disciplines, this book will be of interest to students and scholars in the areas of Japan studies, Politics, International Relations, Security Studies, Government Policy and History"